A Qualitative Approach to the English to Arabic Translation of the Hard News Genre - Mohamad, Jamal; Altamimi, Ahmad (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2019)
This research deals with a type of hard news text as it is expressed, used, or made public in the English newspaper. News stories are basically divided into two types: hard news and soft news. Hard news generally refers to up-to-the-minute news and events that are reported immediately, while soft news is background information or human-interest stories. It serves as a qualitative study to the type of issues it discusses and it is intended to be pointing to areas where further development in translating hard news is much needed. It is a Qualitative research which describes efforts that contribute to the knowledge of the discipline and raises two major questions: (1) how does translation mediate the hard news? (2) How does translation frame news already framed in another language? The research concludes that translating hard news, as a form of written communication, must always be done with a target language and culture in mind.